Resistance levels to non-nucleoside reverse transcriptase inhibitors among pregnant women with recent HIV infection in Malawi. Issue 4 (16th August 2022) - Bello, George; Kagoli, Matthew; Chipeta, Sikhona; Auld, Andrew; Chang, Joy C-W; DeVos, Joshua R; Kim, Evelyn; Mkungudza, Jonathan; Payne, Danielle; Eliya, Michael; Nyirenda, Rose; Jahn, Andreas; et al.
Background: Information on HIV drug resistance (HIVDR) prevalence in people newly diagnosed with HIV is limited. We implemented a cross-sectional study to estimate HIVDR prevalence among pregnant women recently infected with HIV in Malawi. Methods: The HIVDR study was nested within a routine antenatal clinic (ANC) sentinel surveillance survey. Dried blood spot samples were tested for recent infection using a limiting antigen antibody assay together with HIV viral load testing. HIV-1 protease and reverse transcriptase were sequenced using Sanger sequencing. Drug susceptibility was predicted using Stanford HIVdb algorithm (version 8.9). Weighted analysis was performed in Stata 15.1. Results: Of the 21, 642 pregnant women enrolled in the ANC survey, 8.4% (1826/21, 642) tested HIV positive. Of these, 5.0% (92/1826) had recent HIV infection, and 90.2% (83/92) were tested by PCR. The amplification and sequencing success rate was 57.8% (48/83). The prevalence of any HIVDR was 14.6% (5/45) (95% CI: 4.7–36.8%), all of which indicated HIVDR to nonnucleoside reverse transcriptase inhibitors (NNRTIs). HIVDR to nucleoside reverse transcriptase inhibitors was 7.9% (2/45) (95% CI: 1.4–34.6%). Resistance to protease inhibitors currently in use in Malawi was not observed. Conclusions: Despite the low number of cases with presumed TDR, our study hints that resistance to NNRTIs was high, above the 10% target for regimen change. Further investigation is needed to establish the exact magnitude of presumed TDR among women recently infected with HIV. These findings support the transition to an integrase inhibitor-based first-line regimen for patients initiating or on ART.